A catalog of the types of craneflies (Limoniidae and Tipulidae) (Insecta, Diptera) deposited in the Museo Argentino de Ciencas Naturales, Buenos Aires - Bachmann, A.O. (2011)
The type specimens of all accepted categories of twenty-eight names of craneflies (twenty-two of Limoniidae and six of Tipulidae), housed in this Museum are recorded. Specimens labeled as types, but which are not types, or are only very dubiously acceptable as types, are recorded in a separate list, in order to assist in future research. Most of the species here catalogued were described by Dr. C.P. Alexander, based upon specimens from this Museum, sent to him by C. Bruch.